EMOJI IN DIGITAL COMMUNICATION ACROSS CULTURES AND PLATFORMS - Mohira Anvardjanovna Djumabayeva (Modern American Journals, 2025)
The article explores the role of emojis in digital communication across diverse platforms and cultural contexts. Also the paper draws on recent studies to highlight how emojis influence message interpretation, particularly in intercultural exchanges, where their meanings can vary significantly. It argues that emojis are not merely decorative but serve as vital communicative and cultural artifacts.
Keywords: Digital communication, non-verbal cues, intercultural communication, emotional expression, cultural interpretation, online interaction, visual language.